2012
DOI: 10.1128/aac.05693-11
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Interplay between Efflux Pumps and Target Mutations in Development of Antibiotic Resistance in Escherichia coli

Abstract: The emergence of resistance presents a debilitating change in the management of infectious diseases. Currently, the temporal relationship and interplay between various mechanisms of drug resistance are not well understood. A thorough understanding of the resistance development process is needed to facilitate rational design of countermeasure strategies. Using an in vitro hollow-fiber infection model that simulates human drug treatment, we examined the appearance of efflux pump (acrAB) overexpression and target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 39 publications
0
50
1
Order By: Relevance
“…In line with this, it has been demonstrated that deletion of efflux pumps significantly reduces the frequency of emergence of fluoroquinolone-resistant mutant isolates (46,52). A key to preventing fluoroquinolone resistance in P. aeruginosa may therefore be to strictly avoid the use of low doses of fluoroquinolones and thus to preclude the emergence of first-step mutations that confer resistance to fluoroquinolones.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…In line with this, it has been demonstrated that deletion of efflux pumps significantly reduces the frequency of emergence of fluoroquinolone-resistant mutant isolates (46,52). A key to preventing fluoroquinolone resistance in P. aeruginosa may therefore be to strictly avoid the use of low doses of fluoroquinolones and thus to preclude the emergence of first-step mutations that confer resistance to fluoroquinolones.…”
Section: Resultsmentioning
confidence: 74%
“…Although these P. aeruginosa isolates are categorized as susceptible, it remains to be shown that it is safe to treat them with fluoroquinolones (49). The stepwise enrichment of fluoroquinolone resistance mutations has been described previously in several in vitro studies (50,51,52). Mutants at each step are enriched when drug concentrations fall within a specific range called the mutant selection window (1,53).…”
Section: Resultsmentioning
confidence: 99%
“…When resistance was restricted to NAL, we have verified the presence of the PMQR gene qnrS or the presence of one mutation in the chromosomal genes; such genotypes seem insufficient to confer resistance to CIP. However, resistance may not only be determined by the presence of qnrS gene; other factors (not evaluated) such as the possible presence of efflux pumps or organic solvent tolerance may also be responsible for the resistance [37].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the efflux pump is known to be related to resistance to aminoglycosides [18] and FQs [19]. Early low-level LVFX resistance is conferred by efflux pump AcrAB overexpression, followed by high-level resistance mediated by target site mutations [19].…”
Section: Discussionmentioning
confidence: 99%
“…Early low-level LVFX resistance is conferred by efflux pump AcrAB overexpression, followed by high-level resistance mediated by target site mutations [19]. The data in the current study revealed that QRDR mutations in gyrA and parC were more highly correlated with FQ MICs of E. coli for all tested FQs than the four efflux pump genes tested, considering their P-values, even though one of the efflux pump genes (marA) also showed a significant correlation with high MICs to the tested FQs.…”
Section: Discussionmentioning
confidence: 99%